Chronic estrogen deficiency causes gastroparesis by altering neuronal nitric oxide synthase function. - Ravella, K; Al-Hendy, A; Sharan, C; Hale, AB; Channon, K; Srinivasan, S; Gangula, P (2013)
BACKGROUND: Gastroparesis affects predominantly females; however, the biological basis for this gender bias is completely unknown. Several lines of evidence suggest that nitrergic dependent stomach motility function is reduced in diabetic gastroparesis and that nNOS is estrogen-regulated. AIMS: The purpose of this study was to investigate whether reduced levels of estradiol-17β (E2) down-regulates tetrahydrobiopterin (BH4, a cofactor for nNOS dimerization and enzyme activity) biosynthesis and therefore nNOS mediated gastric motility would be impaired in a mouse model of chronic estrogen deficiency, follicle stimulating hormone receptor knock-out female mice (FORKO). METHODS: In-bred 12-week-old female FORKO mice were obtained from our FORKO breeding colony. Gastric emptying was measured in overnight fasting mice. Nitrergic relaxation (AUC/mg tissue) was measured at 2 Hz through electric field stimulation using gastric antrum strips prepared from WT and FORKO mice. Protein expression for nNOSα, BH4 biosynthesis enzymes (GCH-1, DHFR) and estrogen receptors (α, β) were measured in gastric antrum by western blotting. Levels of BH4 and oxidized BH2, B biopterin levels were determined by HPLC. RESULTS: In FORKO, compared to wild type (WT) stomachs we indentified (1) reduced (%) gastric emptying (64 ± 2.5 vs. 77.6 ± 0.88), (2) greater reduction in nitregic relaxation (-0.13 ± 0.012 vs. -0.28 ± 0.012), (3) increased nNOS dimerization (0.48 ± 0.02 vs. 0.34 ± 0.05), (4) decreased NO release whether measured at 24 h (0.6 ± 0.04 vs. 1.7 ± 0.22, p < 0.05) or at 48 h (3.4 ± 0.26 vs. 5.0 ± 0.15, p < 0.05) of incubation, (5) decreased GCH-1 (1.9 ± 0.06 vs. 2.3 ± 0.04), DHFR (1.8 ± 0.14 vs. 2.4 ± 0.07) and ERα (2.7 ± 0.4 vs. 3.9 ± 0.4) and (6) increased oxidized biopterin levels and decreased ratio of BH4 versus BH2 + B. CONCLUSION: We conclude that chronic estrogen deficiency negatively modifies the function of both BH4 and nNOS thereby contributing to the development of gastroparesis in a FORKO mouse model.